2020
DOI: 10.1186/s13567-020-00765-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of influenza A virus and porcine reproductive and respiratory syndrome virus using a novel nurse sow model: a proof of concept

Abstract: The mechanisms of transmission of influenza A virus (IAV) and porcine reproductive and respiratory syndrome virus (PRRSV) in pigs during the pre-weaning period are not fully elucidated. Since viable IAV and PRRSV can be found on the udder skin of lactating sows and the use of nurse sows is a common management practice, we developed a novel nurse sow model to evaluate the transmission of IAV and PRRSV from lactating sows to their adopted piglets. In two studies, we infected pigs with either IAV or PRRSV who the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…While fomite-mediated IAV spread from farmworkers’ clothing and hands to piglets is the most likely cause of IAV transmission, it is also possible that newborn litters are being infected because they are adopted by nurse sows with an IAV contaminated udder [ 14 ]. Nurse sows are lactating sows that have weaned their own litter and are used to adopt piglets at risk of falling behind or dying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While fomite-mediated IAV spread from farmworkers’ clothing and hands to piglets is the most likely cause of IAV transmission, it is also possible that newborn litters are being infected because they are adopted by nurse sows with an IAV contaminated udder [ 14 ]. Nurse sows are lactating sows that have weaned their own litter and are used to adopt piglets at risk of falling behind or dying.…”
Section: Discussionmentioning
confidence: 99%
“…Piglets may be handled during the birthing process and shortly after that to dry them, ensure colostrum intake, prevent injuries, apply iron injections, clip teeth, conduct castration and vaccination, and possibly piglets may be moved into other litters. Some of the management practices, such as cross-fostering and use of nurse sows, in place during this period have been shown to facilitate the spread of IAV among the piglets [ 14 , 15 ]. Furthermore, the transmission of IAV via fomites including contaminated personal protective equipment (PPE) worn by personnel working with pigs has been shown experimentally [ 16 ], and transmission could take place in the presence of both, basic and enhanced biosecurity practices.…”
Section: Introductionmentioning
confidence: 99%
“…When moving piglets between sections, there is a risk of transferring pathogens such as PRRS, and it has been a general belief that moving the sows between sections posed less risk than moving piglets. Garrido-Mantilla et al (2020) showed that both PRRS and influenza A virus can be efficiently transferred by sows via the udder skin from older pigs to younger pigs when using nurse sows, and there is a higher frequency of nurse sows transferring influenza A virus compared with nonnurse sows (Garrido-Mantilla et al, 2021).…”
Section: Health Aspects When Using Nurse Sowsmentioning
confidence: 99%
“…When moving piglets between sections, there is a risk of transferring pathogens such as PRRS, and it has been a general belief that moving the sows between sections posed less risk than moving piglets. Garrido‐Mantilla et al (2020) showed that both PRRS and influenza A virus can be efficiently transferred by sows via the udder skin from older pigs to younger pigs when using nurse sows, and there is a higher frequency of nurse sows transferring influenza A virus compared with nonnurse sows (Garrido‐Mantilla et al, 2021). Management procedures like McREBEL™ ( M anagement C hanges to R educe E xposure to B acteria to E liminate L osses from PRRS ) developed by McCaw (1995) states that cross‐fostering is only allowed within 24 h after birth, and that no sows or piglets can be moved to other sections.…”
Section: Management Considerations Using Nurse Sowsmentioning
confidence: 99%
“…Transport of weaned piglets to distant locations contributes to the dissemination of IAV variants into new regions [16]. Furthermore, there are farm management practices that facilitate IAV dissemination within breeding herds including cross-fostering and use of nurse sows [17,18]. Nurse sows are lactating sows that, when their original litter is weaned, are used to adopt less viable piglets from other litters.…”
Section: Introductionmentioning
confidence: 99%